Evidence for radiation pressure compression in the X-ray narrow-line region of Seyfert galaxies. Issue 1 (13th February 2019) - Bianchi, Stefano; Guainazzi, Matteo; Laor, Ari; Stern, Jonathan; Behar, Ehud
ABSTRACT: The observed spatial and kinematic overlap between soft X-ray emission and the narrow-line region (NLR) in obscured active galactic nuclei (AGNs) yields compelling evidence that relatively low-density gas co-exists with higher density gas on scales as large as 100 s of pc. This is commonly interpreted as evidence for a constant gas pressure multiphase medium, likely produced by thermal instability. Alternatively, radiation pressure compression (RPC) also leads to a density distribution, since a gas pressure (and hence density) gradient must arise within each cloud to counteract the incident ionizing radiation pressure. RPC leads to a well-defined ionization distribution, and a differential emission measure (DEM) distribution with a universal slope of ∼−0.9, weakly dependent on the gas properties and the illuminating radiation field. In contrast, a multiphase medium does not predict the form of the DEM. The observed DEMs of obscured AGN with XMM – Newton Reflection Grating Spectrometer spectra (the CHRESOS sample) are in striking agreement with the predicted RPC DEM, providing a clear signature that RPC is the dominant mechanism for the observed range of densities in the X-ray NLR. In contrast with the constant gas pressure multiphase medium, RPC further predicts an increasing gas pressure with decreasing ionization, which can be tested with future X-ray missions using density diagnostics.